2013
DOI: 10.1111/jasp.12130
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of trust‐betrayal: emotion and relief patterns in different domains

Abstract: This study investigates the emotional responses to betrayal in two domains—social norms and personal acquaintances. The study relies on a newly developed Betrayal‐Domain Questionnaire and the Portrait Value Questionnaire. Study 1 confirmed the existence of two distinct betrayal domains differing in the pattern of emotional response evoked, in the actions that relieve negative emotions and the influence of values on the emotional response. In the social norms domain, betrayal evokes predominantly anger‐related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Specifically, although betrayal has been developed within the realms of interpersonal relationships, we have demonstrated that it can also apply to the case of inter-organizational relationships. Hence, there is room to expand our understanding on betrayal by borrowing more input from the field of social psychology (as well as other disciplines), such as that relating to antecedents (e.g., personality traits of managers), moderators (e.g., penalty assessment), and outcomes (e.g., revenge) (Adams, Luevano, & Jonason, 2014;Chan, 2009;Joskowicz-Jabloner & Leiser, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Specifically, although betrayal has been developed within the realms of interpersonal relationships, we have demonstrated that it can also apply to the case of inter-organizational relationships. Hence, there is room to expand our understanding on betrayal by borrowing more input from the field of social psychology (as well as other disciplines), such as that relating to antecedents (e.g., personality traits of managers), moderators (e.g., penalty assessment), and outcomes (e.g., revenge) (Adams, Luevano, & Jonason, 2014;Chan, 2009;Joskowicz-Jabloner & Leiser, 2013).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Characteristically, responses to betrayal involve blackening the character of the betrayer—and sometimes blackening an entire set of institutions of the same kind as the betrayer—even beyond what is warranted by the action (Jasso, 2008; Joskowicz–Jabloner & Leiser, 2013; Koehler & Gershoff, 2003). This may be especially true in matters of justice (Jasso, 2006).…”
Section: Theorymentioning
confidence: 99%
“…In spite of its ubiquity in social life and the different theoretical perspectives on its potential effectiveness very few studies investigated the effectiveness of overcompensation with regard to important variables such as equality, trust betrayal, trust repair, and cooperation (for some exceptions, see Bies & Tripp, 2006;Joskowicz-Jabloner & Leiser, 2013;Schweitzer, Hershey, & Bradlow, 2006;Stouten, De Cremer, & Van Dijk, 2006). Moreover, the few studies conducted so far focused on very small overcompensations and revealed inconsistent results.…”
Section: Previous Researchmentioning
confidence: 99%